Prevalence of low energy availability in competitively trained male endurance athletes - Lane, A. R.; Hackney, A. C.; Smith-Ryan, A.; Kucera, K.; Registar-Mihalik, J.; Ondrak, K. (Medicina, 2019)
Background and Objectives: Relative energy deficiency in sport (RED-S) has been introduced as a broad-spectrum syndrome leading to possible dysfunction in numerous physiological systems, driven primarily by low energy availability (EA). Research in females has identified specific EA cut-points indicative of risk level for developing physiological and performance disturbances. Cut-points in males have yet to be evaluated. This study examined the prevalence of low EA in competitive (non-elite), recreationally trained (CRT) male endurance athletes. Materials and Methods: Subjects were 108 CRT (38.6 ± 13.8 y; 12.2 ± 5.4 h/wk training) male endurance athletes (runners, cyclists, triathletes) who completed a descriptive survey online via Qualtrics® and returned 3 day diet and exercise training records. EA was calculated from returned surveys and training records. Resting metabolic rate (RMR) and lean body mass (LBM) were estimated from self-reported survey data. Prevalence of risk group was categorized based on the female cut-points: at risk (AR) =30 kcal/kg LBM, moderate risk (MR) = 30-45 kcal/kg LBM, or no risk (NR) =45 kcal/kg LBM. Results: In this sample, 47.2% (n = 51) were classified as AR, 33.3% (n = 36) as MR, and 19.4% (n = 21) as NR for low EA. Cyclists had lower EA (26.9 ± 17.4 kcal/kg LBM, n = 45) than runners (34.6 ± 13.3 kcal/kg LBM, n = 55, p = 0.016) and all other sport categories (39.5 ± 19.1 kcal/kg LBM, n = 8, p = 0.037). Conclusions: The findings indicate this sample had a high prevalence of risk for low EA, at 47.2%. Only 19.4% of participants were at no risk, meaning ~80% of participants were at some degree of risk of experiencing low EA. Cyclists were at greater risk in this cohort of low EA, although why this occurred was unclear and is in need of further investigation. Future research should address whether the current female cut-points for low EA are appropriate for use in male populations.